Recruitment and retention of participants in UK surgical trials: a survey of key issues reported by trial staff - Crocker, JC; Farrar, N; Cook, J; Bulbulia, R (Wiley, 2020)
Background: Recruitment and retention of participants in surgical trials is challenging. Knowledge of the most common and problematic issues will aid future trial design. This study aimed to identify trial staff perspectives on the main issues affecting participant recruitment and retention in UK surgical trials.